Influence of feed ingredient preservation method and protein source inclusion on performance, nutrient digestibility, and environmental impacts of finishing pigs - Shane Maher; Nicholas M. Holden; Torres Sweeney; Kathryn R. Connolly; John V. O’Doherty (Animal Feed Science and Technology, 2026)

Parallel concepts and future opportunities across the biological control and invasion sciences - Ross N. Cuthbert; Nompumelelo Baso; Tressia Chikodza; Candice Coombes; Jane Doherty; Michael Githae; Tamzin C. Griffith; Marco R. Hernandez; Karla M. Jaschke; Michael D. Jukes; David Kinsler; Hugh J. MacIsaac; et al. (Journal of Environmental Management, 2026)

Structure and composition of yellowtail kingfish ( Seriola lalandi ) otoliths: implications for using aquaculture‐reared fish to reconstruct life histories - Belinda K. Goddard; Laura M. Otter; Julian M. Hughes; Fabrice R. A. Jaine; Jasmin C. Martino; Ulrike Troitzsch; Jackson Doherty; Hayden T. Schilling (Journal of Fish Biology, 2025)
Understanding fish life history is essential for effective management of fisheries, but continuous tracking over lifetime temporal scales can be difficult. Fish otoliths contain a natural biogeochemical record of ambient environmental conditions and habitat use over such scales. However, ecological interpretations of these elemental compositions can be influenced by the structural composition of calcium carbonate otoliths, which can vary between wild and aquaculture fish as well as across species. As such, we used in situ confocal micro‐Raman spectroscopy and powder X‐ray diffraction to assess and quantify, respectively, the calcium carbonate polymorphs of the otoliths of aquaculture and wild yellowtail kingfish ( Seriola lalandi ) to validate whether the otoliths from aquaculture fish can be used to interpret patterns seen in the otoliths of wild fish. We then analysed major and minor trace elements using wavelength dispersive X‐ray spectroscopy to investigate the potential habitat use of wild S. lalandi . The elemental composition of S. lalandi otoliths was examined across three cross‐sectioned growth zones: the first (i.e. oldest) annulus (growth ring), the outermost (i.e. most recent) annulus and mid‐way between these. All otoliths were shown to be composed of aragonite, with the exception of small proportions (0.5 wt%) of vaterite in a single wild S. lalandi otolith. This finding indicates that otoliths of aquaculture S. lalandi , reared in known conditions, are appropriate to interpret stable isotope analyses in wild S. lalandi . Wild‐caught S. lalandi otoliths had concentrations of barium and manganese below detectable limits ( S. lalandi were not in estuarine or brackish environments when the analysed annuli were formed, suggesting these environments are not used for spawning.

Cross‐Continental Analysis Shows That Disturbance Effects on Reptile Body Condition Do Not Predict Abundance Responses - Kristina J. Macdonald; Don A. Driscoll; Michael D. Craig; Robert A. Davis; Steven J. Hromada; C. M. Gienger; Lee A. Fitzgerald; Daniel J. Leavitt; Danielle K. Walkup; Rickard Abom; Adrian F. Wayne; Gordon R. Friend; et al. (Global Change Biology, 2025)
Ecological disturbances are discrete events that alter or transform the physical, chemical, or biological characteristics of ecosystems. Disturbance can cause animal populations to decline and, according to the risk‐disturbance hypothesis and population collapse framework, these declines can be predicted by declines in animal body condition. However, no research has empirically examined the general relationship between body condition and abundance, nor their relationship in response to disturbance. We used a combined dataset representing 33 studies and > 42,000 observations of 75 species from Australia, New Zealand, Spain and the United States of America to test predictions relating to the relationship between reptile body condition and abundance. We first investigated the relationship at the site level and then used meta‐analytical models to test whether populations showed linked changes in abundance and body condition in response to disturbance. We further tested whether key environmental and species traits influenced this relationship and whether there was a time‐lagged effect of body condition responses on abundance. We found a positive relationship between mean reptile body condition and abundance at the site level. However, the relationship was largely lost when investigating population responses to disturbance. As such, our results provided no support for the risk‐disturbance hypothesis and limited support for the population collapse framework. Therefore, the impacts of disturbance on reptile body condition cannot be assumed to reflect or predict abundance responses. We provide a new conceptual framework that shows how disturbances can modify or uncouple the relationship between abundance and body condition by influencing underlying drivers, such as predation, competition and resource availability. Monitoring programs that infer population impacts based on changes in body condition should first confirm the relationship between these two variables in the relevant study system.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Maternal PFOS exposure affects offspring development in Nrf2-dependent and independent ways in zebrafish (Danio rerio) - Marjorie Marin; Kate M. Annunziato; Madeline C. Tompach; Wenle Liang; Sarah M. Zahn; Sida Li; Jeffery Doherty; Jonghwa Lee; John M. Clark; Yeonhwa Park; Alicia R. Timme-Laragy (Aquatic Toxicology, 2024)

Experimentally testing animal responses to prescribed fire size and severity - Tim S. Doherty; Daniel F. Bohórquez Fandiño; Darcy J. Watchorn; Sarah M. Legge; Chris R. Dickman (Conservation Biology, 2024)
Deserts are often highly biodiverse and provide important habitats for many threatened species. Fire is a dominant disturbance in deserts, and prescribed burning is increasingly being used by conservation managers and Indigenous peoples to mitigate the damaging effects of climate change, invasive plants, and land‐use change. The size, severity, and patchiness of fires can affect how animals respond to fire. However, there are almost no studies examining such burn characteristics in desert environments, which precludes the use of such information in conservation planning. Using a before‐after control‐impact approach with 20 sampling sites, we studied the outcomes of 10 prescribed burns of varying size (5–267 ha), severity, and patchiness to identify which variables best predicted changes in small mammal and reptile species richness and abundance. Three of the 13 species showed a clear response to fire. Captures increased for 2 species (1 mammal, 1 reptile) and decreased for 1 species (a reptile) as the proportional area burned around traps increased. Two other mammal species showed weaker positive responses to fire. Total burn size and burn patchiness were not influential predictors for any species. Changes in capture rates occurred only at sites with the largest and most severe burns. No fire‐related changes in capture rates were observed where fires were small and very patchy. Our results suggest that there may be thresholds of fire size or fire severity that trigger responses to fire, which has consequences for management programs underpinned by the patch mosaic burning paradigm. The prescribed burns we studied, which are typical in scale and intensity across many desert regions, facilitated the presence of some taxa and are unlikely to have widespread or persistent negative impacts on small mammal or reptile communities in this ecosystem provided that long unburned habitat harboring threatened species is protected.

Accuracy of patient race and ethnicity data in a central cancer registry - Rachel R. Codden; Carol Sweeney; Blessing S. Ofori-Atta; Kimberly A. Herget; Kacey Wigren; Sandra Edwards; Marjorie E. Carter; Rachel D. McCarty; Mia Hashibe; Jennifer A. Doherty; Morgan M. Millar (Cancer Causes & Control, 2024)

A nose for trouble: ecotoxicological implications for climate change and disease in Saiga antelope (S. t. tatarica) - S. T. Mullineaux; J. M. McKinley; N. J. Marks; R. Doherty; D. M. Scantlebury (Environmental Geochemistry and Health, 2024)
In recent decades, Saiga antelope ( Saiga t. tatarica ) mass die-offs have become more common. The mass die-off of 2015 in central Kazakhstan, recorded 140,000 individual deaths across multiple herds. Previously, research has shown atmospheric humidity, the bacterium Pasteurella multocida serotype B, and resultant haemorrhagic septicaemia, were the primary cause. However, other synergistic factors may have impacted this process. Here we use a multivariate compositional data analysis (CoDA) approach to assess what other factors may have been involved. We show a pollutant linkage mechanism where relative humidity and dewpoint temperature combine with environmental pollutants, potentially toxic elements (e.g., Hg, As), complex carbon compounds (e.g., Acetone, Toluene), and inorganic compounds (e.g., CHx, SO 2 ) which affected the Saiga during the calving season (start and peak) and at the onset of the mass die-off. We suggest a mechanism for this process. Upon arrival at their carving grounds, the Saiga experienced a sudden precipitation event, a spike in temperatures, and resultant high humidity occurs. The infectious bacterium P . multocida serotype B then spreads. Further, environmental pollutants contained within steppe soils are released to the air, forming localised smog events, these synergistically combine, and mass die-off occurs.

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Animal mortality during fire - Chris J. Jolly; Chris R. Dickman; Tim S. Doherty; Lily M. van Eeden; William L. Geary; Sarah M. Legge; John C. Z. Woinarski; Dale G. Nimmo (Global Change Biology, 2022)
Earth's rapidly warming climate is propelling us towards an increasingly fire‐prone future. Currently, knowledge of the extent and characteristics of animal mortality rates during fire remains rudimentary, hindering our ability to predict how animal populations may be impacted in the future. To address this knowledge gap, we conducted a global systematic review of the direct effects of fire on animal mortality rates, based on studies that unequivocally determined the fate of animals during fire. From 31 studies spanning 1984–2020, we extracted data on the direct impacts of fire on the mortality of 31 species from 23 families. From these studies, there were 43 instances where direct effects were measured by reporting animal survival from pre‐ to post‐fire. Most studies were conducted in North America (52%) and Oceania (42%), focused largely on mammals (53%) and reptiles (30%), and reported mostly on animal survival in planned (82%) and/or low severity (70%) fires. We found no studies from Asia, Europe or South America. Although there were insufficient data to conduct a formal meta‐analysis, we tested the effect of fire type, fire severity, fire regime, animal body mass, ecological attributes and class on survival. Only fire severity affected animal mortality, with a higher proportion of animals being killed by high than low severity fires. Recent catastrophic fires across the globe have drawn attention to the plight of animals exposed to wildfire. Yet, our systematic review suggests that a relatively low proportion of animals (mean predicted mortality [95% CI] = 3% [1%–9%]) are killed during fire. However, our review also underscores how little we currently know about the direct effects of fire on animal mortality, and highlights the critical need to understand the effects of high severity fire on animal populations.

Multiple-endpoint in vitro carcinogenicity test in human cell line TK6 distinguishes carcinogens from non-carcinogens and highlights mechanisms of action - Katherine E. Chapman; Eleanor C. Wilde; Fiona M. Chapman; Jatin R. Verma; Ume-Kulsoom Shah; Leanne M. Stannard; Anna L. Seager; James A. Tonkin; M. Rowan Brown; Ann T. Doherty; George E. Johnson; Shareen H. Doak; et al. (Archives of Toxicology, 2021)
Current in vitro genotoxicity tests can produce misleading positive results, indicating an inability to effectively predict a compound’s subsequent carcinogenic potential in vivo. Such oversensitivity can incur unnecessary in vivo tests to further investigate positive in vitro results, supporting the need to improve in vitro tests to better inform risk assessment. It is increasingly acknowledged that more informative in vitro tests using multiple endpoints may support the correct identification of carcinogenic potential. The present study, therefore, employed a holistic, multiple-endpoint approach using low doses of selected carcinogens and non-carcinogens (0.001–770 µM) to assess whether these chemicals caused perturbations in molecular and cellular endpoints relating to the Hallmarks of Cancer. Endpoints included micronucleus induction, alterations in gene expression, cell cycle dynamics, cell morphology and bioenergetics in the human lymphoblastoid cell line TK6. Carcinogens ochratoxin A and oestradiol produced greater Integrated Signature of Carcinogenicity scores for the combined endpoints than the “misleading” in vitro positive compounds, quercetin, 2,4-dichlorophenol and quinacrine dihydrochloride and toxic non-carcinogens, caffeine, cycloheximide and phenformin HCl. This study provides compelling evidence that carcinogens can successfully be distinguished from non-carcinogens using a holistic in vitro test system. Avoidance of misleading in vitro outcomes could lead to the reduction and replacement of animals in carcinogenicity testing.

Seasonal changes in basking shark vertical space use in the north-east Atlantic - P. D. Doherty; J. M. Baxter; B. J. Godley; R. T. Graham; G. Hall; J. Hall; L. A. Hawkes; S. M. Henderson; L. Johnson; C. Speedie; M. J. Witt (Marine Biology, 2019)
Mobile marine species can exhibit vast movements both horizontally and vertically. Spatial analysis of vertical movements may help improve an understanding of the processes that influence space use. Previously, vertical space use of basking sharks ( Cetorhinus maximus ) in the north-east Atlantic described movements largely within waters of the continental shelf during summer and autumn months, with few records of detailed vertical behaviour during winter. We use archival satellite telemetry data from 32 basking sharks (12 females, 6 males, and 14 of unknown sex measuring 4–5 m ( n = 6), 5–6 m ( n = 10), 6–7 m ( n = 7), 7–8 m ( n = 8), and 8–9 m ( n = 1) estimated total length) tracked over 4 years (2012–2015). The satellite tags provided depth and temperature data for a cumulative 4489 days (mean 140 ± 97 days per shark, range 10–292 days) to describe vertical space use and thermal range of basking sharks in the north-east Atlantic. Basking sharks exhibit seasonality in vertical space use, revealing repeated ‘yo-yo’ movement behaviour with periods of occupancy at depths greater than 1000 m in late winter/early spring. Describing seasonal vertical space use in marine megavertebrates can increase knowledge of movements throughout their environment including physiological and morphological constraints to movement, nutrient transfer, and overlap with anthropogenic threats to inform future conservation strategies.

Genetic modifiers of radon-induced lung cancer risk: a genome-wide interaction study in former uranium miners - Albert Rosenberger; Rayjean J. Hung; David C. Christiani; Neil E. Caporaso; Geoffrey Liu; Stig E. Bojesen; Loic Le Marchand; Ch. A. Haiman; Demetrios Albanes; Melinda C. Aldrich; Adonina Tardon; G. Fernández-Tardón; et al. (International Archives of Occupational and Environmental Health, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

A novel, integrated in vitro carcinogenicity test to identify genotoxic and non-genotoxic carcinogens using human lymphoblastoid cells - Eleanor C. Wilde; Katherine E. Chapman; Leanne M. Stannard; Anna L. Seager; Katja Brüsehafer; Ume-Kulsoom Shah; James A. Tonkin; M. Rowan Brown; Jatin R. Verma; Ann T. Doherty; George E. Johnson; Shareen H. Doak; et al. (Archives of Toxicology, 2018)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

STC1 expression is associated with tumor growth and metastasis in breast cancer - Andy C-M Chang; Judy Doherty; Lily I. Huschtscha; Richard Redvers; Christina Restall; Roger R. Reddel; Robin L. Anderson (Clinical & Experimental Metastasis, 2015)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Postglacial vegetation and climate dynamics in the Seymour‐Belize Inlet Complex, central coastal British Columbia, Canada: palynological evidence from Tiny Lake - Jennifer M. Galloway; Christine T. Doherty; R. Timothy Patterson; Helen M. Roe (Journal of Quaternary Science, 2009)
A pollen‐based study from Tiny Lake in the Seymour‐Belize Inlet Complex of central coastal British Columbia, Canada, permits an evaluation of the dynamic response of coastal temperate rainforests to postglacial climate change. Open Pinus parklands grew at the site during the early Lateglacial when the climate was cool and dry, but more humid conditions in the later phases of the Lateglacial permitted mesophytic conifers to colonise the region. Early Holocene conditions were warmer than present and a successional mosaic of Tsuga heterophylla and Alnus occurred at Tiny Lake. Climate cooling and moistening at 8740 ± 70 14 C a BP initiated the development of closed, late successional T. heterophylla –Cupressaceae forests, which achieved modern character after 6860 ± 50 14 C a BP, when a temperate and very wet climate became established. The onset of early Holocene climate cooling and moistening at Tiny Lake may have preceded change at more southern locations, including within the Seymour‐Belize Inlet Complex, on a meso‐ to synoptic scale. This would suggest that an early Holocene intensification of the Aleutian Low pressure system was an important influence on forest dynamics in the Seymour‐Belize Inlet Complex and that the study region was located near the southern extent of immediate influence of this semi‐permanent air mass. Copyright © 2008 John Wiley & Sons, Ltd.

Radiative forcing from surface NO x emissions: spatial and seasonal variations - R. G. Derwent; D. S. Stevenson; R. M. Doherty; W. J. Collins; M. G. Sanderson; C. E. Johnson (Climatic Change, 2008)

Multi-proxy evidence of postglacial climate and environmental change at Two Frog Lake, central mainland coast of British Columbia, Canada - Jennifer M. Galloway; R. Timothy Patterson; Christine T. Doherty; Helen M. Roe (Journal of Paleolimnology, 2007)

Turbulent mixing and mesoscale distributions of late‐stage fish larvae on the NW Shelf of Western Australia - M. G. MEEKAN; J. H. CARLETON; C. R. STEINBERG; A. D. MCKINNON; R. BRINKMAN; P. J. DOHERTY; A. HALFORD; S. DUGGAN; L. MASON (Fisheries Oceanography, 2006)
Light traps were deployed to describe vertical and cross‐shelf distributions of late‐stage larval fishes during five cruises in each of the 1997/98 and 1998/99 summers in the region of the Gulf of Exmouth on the southern North West Shelf of Western Australia. At each light trap station on a cross‐shelf transect we measured water temperature, salinity and chlorophyll a and used vertical plankton tows to estimate zooplankton biomass and copepod abundance. Current meters were deployed on moorings near the transect and the data used to model flows and mixing on the NW Shelf and in the Gulf. The majority of reef, pelagic and baitfish larvae (81, 83 and 66% respectively) were collected at only two stations that marked the boundary between stratified waters offshore and well‐mixed water within the Gulf. Most baitfishes (primarily Spratelloides spp.) were captured by traps deployed near the seabed, while reef fishes (mostly pomacentrids, lethrinids and siganids) and pelagic species (mostly scombrids and carangids) were captured in traps deployed near surface. Catch composition varied between summers with 64% of baitfishes collected in the first summer, while the majority of reef and pelagic fishes (81 and 80% respectively) were captured in the second summer. Modelling of circulation showed that the velocity of tidal currents was enhanced by constriction of flow between NW Cape and South Muiron Island and by shallowing of the shelf. Flood‐tide intrusions of water allowed the thermocline to move up the continental shelf, upwelling cool nutrient‐rich water that was then mixed throughout the entire water column at stations in the mouth of the Gulf. This upwelling and mixing resulted in higher chlorophyll a concentrations and copepod abundances either as a result of local in situ growth or advection/aggregation processes, and may account for the great abundances of late‐stage fish larvae in the mouth of the Gulf.

AGAGE Observations of Methyl Bromide and Methyl Chloride at Mace Head, Ireland, and Cape Grim, Tasmania, 1998–2001 - P. G. Simmonds; R. G. Derwent; A. J. Manning; P. J. Fraser; P. B. Krummel; S. O'Doherty; R. G. Prinn; D. M. Cunnold; B. R. Miller; H. J. Wang; D. B. Ryall; L. W. Porter; et al. (Journal of Atmospheric Chemistry, 2004)

Toxicity Assessment of a Former Manufactured Gas Plant - A. S. Ferguson; R. Doherty; M. J. Larkin; R. M. Kalin; V. Irvine; U. S. Ofterdinger (Bulletin of Environmental Contamination and Toxicology, 2003)

Second primary tumors in patients with upper aerodigestive tract cancers: joint effects of smoking and alcohol (United States) - Kim-Anh Do; Marcella M. Johnson; Dorota A. Doherty; J. Jack Lee; Xi Feng Wu; Qiong Dong; Waun K. Hong; Fadlo R. Khuri; Karen K. Fu; Margaret R. Spitz (Cancer Causes & Control, 2003)

Hydroxyl Radical Concentrations Estimated from Measurements of Trichloroethylene during the EASE/ACSOE Campaign at Mace Head, Ireland during July 1996 - R. G. Derwent; N. Carslaw; P. G. Simmonds; M. Bassford; S. O'Doherty; D. B. Ryall; M. J. Pilling; A. C. Lewis; J. B. McQuaid (Journal of Atmospheric Chemistry, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Objectives and background to the 1994 Franco-Australian expedition to Taiaro Atoll (Tuamotu Archipelago, French Polynesia) - R. Galzin; S. Planes; M. Adjeroud; C. Chauvet; P. J. Doherty; J. Poupin (Coral Reefs, 1998)